2019
DOI: 10.1080/00063657.2019.1585749
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive capacity of Monk ParakeetsMyiopsitta monachusis higher in their invasive range

Abstract: We provide detailed breeding parameters for the population of monk parakeets, Myiopsitta monachus, in Barcelona, Spain, based on data collected for 651 nests over five breeding seasons. This invasive population has a high reproductive capacity compared to the native range: fledging success was double, the percentage of pairs attempting second broods three times higher, and 55% of one-year old birds bred compared to almost zero in South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…The fact that most of the non-native populations are urban may be explained by predation release, which allows a higher breeding success in their invaded urbanised habitats than in their native ranges, as was also shown for the highly invasive rose-ringed parakeet Psittacula krameri [97]. In fact, recent work has demonstrated that the breeding success of monk parakeets is twice as high in a Spanish city than in its native range [95]. Other hypotheses, such as competition or parasite release, seem unlike to explain the high success of monk parakeets in urban areas.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…The fact that most of the non-native populations are urban may be explained by predation release, which allows a higher breeding success in their invaded urbanised habitats than in their native ranges, as was also shown for the highly invasive rose-ringed parakeet Psittacula krameri [97]. In fact, recent work has demonstrated that the breeding success of monk parakeets is twice as high in a Spanish city than in its native range [95]. Other hypotheses, such as competition or parasite release, seem unlike to explain the high success of monk parakeets in urban areas.…”
mentioning
confidence: 83%
“…Other hypotheses, such as competition or parasite release, seem unlike to explain the high success of monk parakeets in urban areas. Contrarily to the secondary cavity-nesting rose-ringed parakeet, which competes with native species for nest holes [52], monk parakeets are unique among parrots as they build their own nests using wood sticks on trees and artificial substrates such as power pylons and roofs [65,95], thus avoiding competition for nest sites. Regarding parasite release, monk parakeets gain novel parasites from the recipient community in its invaded range while also maintain parasites from its native range [7,19,70].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Argentina, monk parakeet depredation by white-eared opossums ( Didelphis albiventris ) and Patagonian green racer ( Philodryas patagoniensis ) has been described [30]. In Santiago, urban park managers mentioned that black rats ( Rattus rattus ) were observed climbing tree trunks, entering monk parakeets nests, and depredating monk parakeets, something that has also been described in Barcelona, Spain [48]. Lastly, we have observed the use of thorny branches of the native Roman cassie ( Acacia caven ) in monk parakeets’ chamber entrances, likely as a defense barrier to these and other predators.…”
Section: Discussionmentioning
confidence: 99%
“…Their widespread success is attributed to behavioral and ecological traits, such as their flexible diet, gregarious behavior, tolerance to human disturbance and novel habitats, and high population growth rates as a result of their reproductive strategies [1,5,12,46,47]. In fact, recent studies have recognized the higher invasive success of monk parakeets on their invasive range, compared to their native habitats [48].…”
Section: Methodsmentioning
confidence: 99%